IF MAHAN RAN THE GREAT PACIFIC WAR : An Analysis of World War II Naval Strategy - Adams, John A., 1949- (Indiana University Press, 2008)
Alfred Thayer Mahan's The Influence of Sea Power upon History (1660–1783) was one of the most influential books on military strategy in the first half of the 20th century. A core text in the naval war colleges of the United States, Britain, and Japan, Mahan's book shaped doctrine for the conduct of war at sea. Adams uses Mahan's ideas to discuss the great Pacific sea battles of World War II and to consider how well they withstood the test of actual combat. Reexamining the conduct of war in the Pacific from a single analytic viewpoint leads to some surprising conclusions about the Japanese attack on Pearl Harbor, the Doolittle Raid, the Battle of the Coral Sea, the recapture of the Philippines, and the submarine war. Naval historians and armchair strategists alike will find much food for thought in these engrossing pages.